Ochrona gruntów rolnych, czyli o sprzeczności interesów i ich kojarzeniu - Pańko, Walerian (Wydział Prawa i Administracji UAM, 1985)
The aim of the present article is to answer the question if the new farm- and forest-land Protection Act of 1982 is an expression of excessive farming privileges "at the cost" of the non-agricultural sectors of the national economy. With this purpose in mind, the author turns our attention to the different interests taken into account by the Act, at the subjects expressing those interests, and at the ways of protecting and the methods of reconciling them. In the area of farmland protection, there appear side by side interests formulated in terms of a branch and a territorial perspective. The "branch" ones appear in the foreground. They may be presented in a diagram as: farming versus other different spheres of socio-economic life. The "territorial" interests are differentiated into national, regional and local ones. Finally, there appear, side by side, the interests of the farm and those of the productive plant. (In conclusion, the author states that the farmland Protection Act should not be suspected of an excessive departmental particularism. Its solutions allow us to speak of a progres in farmland protection, but the progress should be evaluated „as at best very modest.
The Protection of Farm-land or on Contradictory Interests and Their Reconciliation